Divergence and Parametric Instability of Belts by using Bolotin Method - Ismail, Mahmud R. (Nahrain University College of Engineering Journal, 2014)
Belt is a traveling continuoussystem.Such a system can subjected to astatic divergence and parametricinstability. This depend on whether thesystem parameters are constant orvarying with the time ,respectively .Inthis paper ,instability problem is solvedanalytically .Bolotin method is used toevaluate the boundaries which separatethe stable and instable regions.Thepresent solution is checked with anothersolution available in the literature wherethe Variation principle is used .Theresults showed a good agreement wherethe maximum error do not exceed 5%.The effect of belt tension andtransmitting speed on stability andnatural frequency are studied .Theresults show that increasing belt tensioncan improve both buckling andparametric instability. Whilst, increasingthe speed or its mean value is limited tocritical values to avoid buckling orparametric instability, respectively.